XX դարի առաջին կեսի եգիպտական գրական արձակի լեզուն. գրական արաբերենի և բարբառի կիրառումը - Կարապետյան, Նաիրա («Զանգակ - 97»)
Though the Literary Arabic is the same official language in many countries, it has many dialects for various nations. An Egyptian understands what Iraqee writes, but he doesn't understand what he says. Even in the same country there is a huge number of people who doesn't understand Literary Arabic. So it is a big problem for writers how to write a novel in order to make it clear for wide mass of people. If they write in the Literary, it will be unclearable for usual people. If they write in the dialect, it will make novels simple. So, at the beginning of the 20th Century there were a movement which helped to synthese these two displays of the same language. The writers began to write dialogues in dialect and the author's speech in the Literary. It makes dialects more up-to -life and understandable for Egyptians, who does not know the Literary language. They thought that a hero from common people must speak a language of common people - that is to say in dialect.
Keywords: Բանասիրություն; Լեզվաբանություն